Provable security : 8th International Conference, ProvSec 2014, Hong Kong, China, October 9-10, 2014. Proceedings - Liu, Joseph K.; Hui, Lucas C. K.; Yiu, Siu Ming; Chow, Sherman S. M. (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 8th International Conference on Provable Security, ProvSec 2012, held in Chengdu, China, in September 2012. The 20 full papers and 7 short papers presented together with 2 invited talks were carefully reviewed and selected from 68 submissions. The papers are grouped in topical sections on fundamental, symmetric key encryption, authentication, signatures, protocol, public key encryption, proxy re-encryption, predicate encryption, and attribute-based cryptosystem.